Exploring Muslim Youth Perceptions of Gender Imitation And Transwoman Representation in Digital Media - Suhertina, Suhertina; Hasbullah, Hasbullah; Ahmad, Raja Rahima Munawarah Raja; Hasgimianti, Hasgimianti (Indonesian Journal of Counseling and Development, 2025)
The rise of gender representation and transgender identity in digital media especially through gender-imitation content on TikTok, Instagram, and YouTube has influenced how Muslim adolescents interpret the boundaries between entertainment and morality. This study explores Muslim youths’ perceptions of gender-imitation and transwoman representation on social media using Husserl’s phenomenological approach. Fifteen Muslim adolescents aged 13–15 who actively follow gender-imitation accounts participated in semi-structured interviews. Data were analyzed using the Colaizzi method with validation through member checking and source triangulation. The findings reveal a core tension between entertainment and moral judgment. While many adolescents perceive gender-imitation content as humorous and creative entertainment, others interpret it as a moral deviation conflicting with Islamic values. This ambivalence reflects a negotiation between digital culture and religious principles, showing that exposure to such content simultaneously entertains and challenges moral reasoning. The study underscores the need for Islamic values-based media literacy to help Muslim adolescents critically interpret gender representation without diminishing their moral and spiritual sensitivity.